System of Compensation and Variance of Cage Crews (ABK) Income in UD - Nurinaya Nurinaya; Siti Marhumi; Nur Mayasari; Nurcahya Ningsih; Muh Fadhil Arrijal (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study aims to provide empirical evidence of the compensation system and income variance for Cage Crews (ABK) at UD. Turiolo before and after transitioning from an open to a closed house system, along with assessing the resulting income increases. Methodology/approach: This research adopts a quantitative descriptive approach, utilizing a paired sample t-test for data analysis. Data collection involved interviews with business owners and four crew members and documentation of compensation records across maintenance cycles. Results/findings: The findings revealed a significant increase in ABK income after the implementation of the closed house system. The performance-based compensation system is directly correlated with higher income levels achieved through improved operational efficiency. Conclusion: The MSME performance of social media in TOS Lubuklinggau showed a 45.3% sales increase, especially in culinary and fashion products. This study reveals the potential of digital marketing and the need for wider adoption and stakeholder support. Limitations: The study focused solely on one broiler chicken farm in Gowa Regency, limiting the generalizability of the findings to other farms or regions. Future studies should include a broader sample across different farming systems and geographical areas. Contribution: This research highlights the critical role of compensation systems in improving worker income within the poultry farming industry and provides evidence of the economic benefits of adopting modern cage systems, such as the closed house model.